2023
DOI: 10.3390/biomedicines11082196
|View full text |Cite
|
Sign up to set email alerts
|

Identification of NOX4 as a New Biomarker in Hepatocellular Carcinoma and Its Effect on Sorafenib Therapy

Abstract: To improve the survival of patients with hepatocellular carcinoma (HCC), new biomarkers and therapeutic targets are urgently needed. In this study, the GEO and TCGA dataset were used to explore the differential co-expressed genes and their prognostic correlation between HCC and normal samples. The mRNA levels of these genes were validated by qRT-PCR in 20 paired fresh HCC samples. The results demonstrated that the eight-gene model was effective in predicting the prognosis of HCC patients in the validation coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…25 In addition, earlier studies concluded that cirrhotic livers generate immunemediated cancer fields, as evidenced by multiple gene signatures derived from cirrhotic liver tissues, which is conducive to the progression of HCC. [26][27][28][29] Larger tumor size is another independent predictor for a poor prognosis in proliferative HCC. Larger tumors have been reported to exhibit greater intratumoral heterogeneity, resulting in a higher risk of drug resistance and a worse prognosis.…”
mentioning
confidence: 99%
“…25 In addition, earlier studies concluded that cirrhotic livers generate immunemediated cancer fields, as evidenced by multiple gene signatures derived from cirrhotic liver tissues, which is conducive to the progression of HCC. [26][27][28][29] Larger tumor size is another independent predictor for a poor prognosis in proliferative HCC. Larger tumors have been reported to exhibit greater intratumoral heterogeneity, resulting in a higher risk of drug resistance and a worse prognosis.…”
mentioning
confidence: 99%